A comparative analysis of available features and Web 2.0 tools on selected Nigerian and South African university library websites. Issue 3 (6th June 2016) - Tella, Adeyinka; Oladapo, Oyegunle John
Abstract : Purpose: The study aims to present a comparative analysis of available Web 2.0 tools in library websites of selected Nigerian and South African universities. Design/methodology/approach: Content analysis was adopted as the design for the study. Twenty university library websites comprising ten top-ranking Nigerian universities and ten top-ranking South African universities were sampled for data collection. Five research questions developed and answered. Findings: The findings show that the use of Web 2.0 tools in the selected universities is encouraging. There are more Web 2.0 tools available on the South African university library websites. The South African university libraries are ahead of their Nigerian counterparts in terms of the integration of Web 2.0 tools, e-resources and e-databases and provide platforms for easy retrieval of information by their users. There are more e-resources available on the South African university library websites compared with their Nigerian counterparts. e-Journals are the most available e-resources in the selected university library websites of both countries. Similarly, more academic e-databases are available on the South African university library websites, whereas only few are listed on the web pages of the selected Nigerian university library websites. Research limitations/implications: Because available studies seem to ignore the possibility of comparing one university library's website with another, conducting a study such as this will provide an insight and idea on the types of features, tools and applications to be included on university library websites. This will be useful for university whose library is planning to develop a website. Originality/value: Because of the wide variation reported in this study concerning available tools and resources on the university library websites in South Africa and Nigeria, it is recommended that African universities should come up with a standard that will mandate universities to have a certain number of tools identified in this study on their various university websites.